How Hybrid Breakdown Can Be Handled in Rice Crossbreeding? - Matsubara, Kazuki (Frontiers in Plant Science, 2020)
In crosses between genetically divergent parents, traits such as weakness and sterility often segregate in later generations. This hybrid breakdown functions as a reproductive barrier and reduces selection efficiency in crossbreeding. Here, I provide an overview of hybrid breakdown in rice crosses and discuss ways to avoid and mitigate the effects of hybrid breakdown on rice crossbreeding, including genomics-assisted breeding.